The Career Guidance Activities for Students of State Vocational High School 1 Pebayuran Bekasi Regency - Medi Nopiana; Sri Setiawati Utami; Muhammad Nasim Harahap (Universitas Negeri Semarang, 2025)
The implementation of this career guidance is based on the importance of helping direct students to prepare their future career plans. Universitas Singaperbangsa Karawang must contribute to the problems faced by the community and other stakeholders around their campus. Given the lack of career guidance activities in high schools in the Bekasi Regency area, the community service team determined the location of the community service activity at State Vocational High School 1 Pebayuran, Bekasi Regency. This activity was combined with the Real Work Lecture of Universitas Singaperbangsa Karawang students in Sumberurip Village, Pebayuran Subdistrict, Bekasi Regency. This activity was held offline on Monday, January 20, 2025. The method of implementing the activity used the counseling method. This activity provides input and suggestions to students according to their choices (working or pursuing higher education) by considering opportunity costs.